Edukasi HIV AIDS Guna Mencegah Stigma Remaja di Puskesmas Harapan - Fathia Fahkri Inayati Said; Lisma Natalia Br Sembiring; Yance Ronald Rainuny; Yestiani Norita Joni (NuCSJo : Nusantara Community Service Journal, 2026)
HIV/AIDS remains a serious health problem, not only from a medical perspective but also socially, especially related to stigma in society. Adolescents, as a productive age group, often have limited and incorrect knowledge about HIV/AIDS, which can lead to negative stigma toward people living with HIV/AIDS. This community service activity aimed to improve adolescents' knowledge and reduce stigma through health education at Harapan Health Center. The method used was health education with a pretest-posttest approach involving 24 adolescents. The materials included the definition of HIV/AIDS, modes of transmission, prevention, and the impact of stigma. The results showed an increase in participants' knowledge after the education, as indicated by the comparison of pretest and posttest scores. In addition, participants showed a more positive attitude toward people living with HIV/AIDS. In conclusion, health education is effective in improving knowledge and reducing stigma among adolescents regarding HIV/AIDS.